Philip DuMont letter to James Peters regarding Savannah Sparrow specimens, May 16, 1934 - DuMont, Philip A. (Philip Atkinson), 1903-1996 (1934)
Letter from Philip DuMont to James Peters dated May 16, 1934. DuMont sends more Savannah Sparrow specimens to Peters for review, and discusses some birds he has recently sighted in Iowa. This document is in response to a letter from Peters: https://n2t.net/ark:/87292/w96688q00.